Hybrid nanoflowers bearing tetraphenylporphyrin assembled on copper(II) or cobalt(II) inorganic material: A green efficient catalyst for hydrogenation of nitrobenzenes in water. (15th January 2020) - Dayan, Serkan; Altinkaynak, Cevahir; Kayaci, Nilgün; Doğan, Şengül Dilem; Özdemir, Nalan; Ozpozan, Nilgün Kalaycioglu
Abstract : Simple fabrication of organic–inorganic hybrid nanoflowers (TPP@CuhNfs and TPP@CohNfs) was achieved with tetraphenylporphyrin (TPP) as organic counterpart and Cu 2+ or Co 2+ ions as inorganic materials via a green route, with lower cost and controlled pH. The effect of pH levels and TPP concentrations on the morphology of the TPP@CuhNfs and TPP@CohNfs materials was examined by scanning electron microscopy (energy‐dispersive X‐ray [EDX]). The formation and chemical structures of TPP@CuhNfs and TPP@CohNfs were evaluated using Fourier transform infrared. Elemental analyses of these hybrid nanoflowers were carried out by EDX. The fabricated TPP@CuhNfs and TPP@CohNfs nanomaterials under optimum conditions act as effective reusable catalysts for the hydrogenation of nitroanilines in aqueous media at ambient temperature. The time‐dependent hydrogenation can be easily monitored spectrophotometrically and verified by 1 H‐nuclear magnetic resonance. These types of the catalytic reaction or system are recorded to be useful toward the hydrogenation of nitroanilines, regardless of the position and type of substrate. Moreover, TPP@CuhNfs and TPP@CohNfs catalysts demonstrated a type of metal ions‐dependent catalytic efficiency toward hydrogenation of nitroanilines (organic pollutants), with TPP@CuhNfs found to be more effective than TPP@CohNfs. However, both catalysts containing Cu 2+ and Co 2+ ions showed good performance and can be reused at least five times without a significant decline in yield. The presented approach based on hybrid nanoflowers provides as a low cost and ecofriendly method (green route) for different catalytic hydrogenations. Abstract : The catalytic activity of the synthesized tetraphenylporphyrin copper hybrid nanoflowers (TPP@CuhNfs) and tetraphenylporphyrin cobalt hybrid nanoflowers (TPP@CohNfs) was investigated in the hydrogenation of the nitroanilines as organic pollutants in water. The catalytic performance of materials has been found to be related to the metal ion types of the hybrid nanoflowers. The easily installable reaction, short reaction time, and an aqueous medium at ambient temperature for the hydrogenation of nitrobenzenes make the catalytic system sustainable, eco‐friendly, and green for industrial applications.